A novel method for contact analysis of rubber and various surfaces using micro-computerized-tomography. (August 2016) - Kriston, András; Fülöp, Tibor; Isitman, Nihat Ali; Kotecký, Ondřej; Tuononen, Ari J.
Abstract: The experimental analysis of the contact state in a tribosystem is of great importance in the study of contact mechanics. In order to make a realistic analysis on the micro scale, it is desirable to keep the tribosystem unperturbed, i.e., without any surface treatment or incorporation of a third body to facilitate the analysis. This study presents the use of a novel technique, micro-computerized tomography (micro-CT), in the investigation of contact between rubber compounds and various counter-surfaces. The goal of this study was to further advance the use of micro-CT in contact mechanics. Specific image analysis techniques were developed in order to process micro-CT images of contact pairs formed by rubber compounds of different hardness levels against counter-surfaces with varying surface roughness and mechanical properties. The micro-CT method has been shown to allow the direct visualization and precise quantification of the real area of contact without altering the original characteristics of the contact pair.